Biosensors for healthcare: current and future perspectives. Issue 3 (March 2023) - Kim, Eun Ryung; Joe, Cheulmin; Mitchell, Robert J.; Gu, Man Bock
Highlights: The capability and diversity of biosensors for human healthcare have grown tremendously, with novel approaches continually being developed. Increased sensitivities of biosensors for in vitro diagnosis have been achieved using nanomaterials and nanotechnologies, while paper-based biosensor devices are a cost-effective alternative, all while maintaining high sensitivities and adapting ingenious design implementations. While clustered regularly interspaced short palindromic repeats (CRISPR)-based biosensors have traditionally been used to detect nucleic acids, recent advances using bioreceptors have expanded their capabilities to non-nucleic acid targets. Wearable biosensors now boast multiplex capabilities and are even battery-free and wireless. Continuous monitoring and wearable biosensors are both considered to be key diagnostic tools for artificial intelligence-assisted human healthcare in the near future. Abstract: Biosensors are utilized in several different fields, including medicine, food, and the environment; in this review, we examine recent developments in biosensors for healthcare. These involve three distinct types of biosensor: biosensors for in vitro diagnosis with blood, saliva, or urine samples; continuous monitoring biosensors (CMBs); and wearable biosensors. Biosensors for in vitro diagnosis have seen a significant expansion recently, with newly reported clustered regularly interspaced short palindromic repeats (CRISPR)/Cas methodologies and improvements to many established integrated biosensor devices, including lateral flow assays (LFAs) and microfluidic/electrochemical paper-based analytical devices (μPADs/ePADs). We conclude with a discussion of two novel groups of biosensors that have drawn great attention recently, continuous monitoring and wearable biosensors, as well as with perspectives on the commercialization and future of biosensors.